DBDx-based drug combinations show highly potent therapeutic efficacy against human pancreatic cancer xenografts in athymic mice. Issue 8 (2nd August 2020) - Zheng, Yan-Bo; Zhang, Meng-Ran; Li, Yi; Liu, Xiu-Jun; Zhen, Yong-Su
ABSTRACT: Previous studies have shown that DBDx, a combination consisting of dipyridamole, bestatin and dexamethasone is highly effective against several cancer xenografts in athymic mice. Here the therapeutic effects of DBDx and its combination with gemcitabine or capcitabine against human pancreatic cancer xenografts and the mechanism were studied. In vivo experiments performed in athymic mice showed that the antitumor efficacy of DBDx was much stronger than that of gemcitabine or capecitabine alone. Notably, the combination of DBDx and gemcitabine or capcitabine further enhanced the efficacy. In the case of DBDx (242 mg/kg) plus gemcitabine (100 mg/kg), tumor weight decreased about 97.7%, and tumor sizes were shrinking during the treatment. In the case of DBDx (242 mg/kg) plus capecitabine (718.7 mg/kg), tumor weight decreased about 94.9%. Moreover, DBDx and its combinations obviously prolonged theoverall survival of mice compared with gemcitabine or capcitabine alone. DBDx-based drug combination therapy showed no obvious systematic toxicity. The gene expression profile analysis showed that the genes changed by DBDx were related to immune system and tumor vasculature. The result of protein array showed that the changed proteins in the serum of treated mice were related to immune and inflammation system. These results show that DBDx-based drug combinations, a new strategy which integrates the use of low-cytotoxic drugs and cytotoxic chemotherapeutics, are highly effective regimens against human pancreatic cancer in athymic mice at well tolerated doses. DBDx-based drug combination therapy might provide new options for the treatment of pancreatic cancer.